Advancing Sustainability in the Nigerian Construction Sector: Evaluating the Benefits, Challenges, and Long-Term Impacts of Energy-Efficient Technologies - Unegbu, Hyginus Chidiebere Onyekachi; Yawas, D. S.; Dan-asabe, B; Alabi, A. A. (Jurnal Pengabdian KOLABORATIF, 2025)
This study investigates the impact of energy-efficient technologies (EETs) on the Nigerian construction sector, focusing on their benefits, barriers to adoption, and sustainability implications. Using a mixed-methods approach, data were collected through structured surveys, semi-structured interviews, and case studies involving construction professionals and stakeholders. The findings reveal that EETs offer significant economic, environmental, and social benefits, including reduced operational costs, lower energy consumption, and improved occupant comfort. However, their adoption in Nigeria is hindered by high upfront costs, lack of technical expertise, insufficient awareness, and weak regulatory frameworks. These challenges align with findings from other developing countries, underscoring the need for targeted interventions. The study also highlights the potential of EETs to contribute to sustainable development by reducing greenhouse gas emissions and supporting the achievement of the United Nations Sustainable Development Goals (SDGs). Case studies of successful projects in Nigeria provide valuable insights into best practices, emphasizing the importance of strong leadership, stakeholder collaboration, and access to financing. Based on the findings, the study recommends policy interventions, capacity-building initiatives, public awareness campaigns, and regulatory reforms to promote the adoption of EETs. Future research should explore innovative financing mechanisms, the role of digital technologies, and the impact of occupant behavior on energy efficiency. This study contributes to the growing body of literature on sustainable construction practices and provides a foundation for further investigations into the adoption and impact of EETs in Nigeria and similar contexts.
Keywords: barriers to adoption; energy-efficient technologies; sustainability implications; sustainable construction